Evaluation of bioengineering soil erosion control techniques in standard USLE plots - Mohd Soom, Mohd Amin; Yong, Hong Liang; Bakar, Mohamed Rashidi (Universiti Putra Malaysia, 1999)
An erosion control study on Serdang series soil was conducted in standard USLE plots at DBAE Field Station, UPM. The bioengineering erosion control techniques include vetiver (Vetiveria zizanioides), legume (Arachis pintoi), spot turfing and close turfing with cowgrass (Axonopus compressus), hydroseeding and few combinations of hydroseeding with biomats. A plot was left bare as a control. Close turfing gave better soil protection than the other grass species, reducing soil loss by 99% compared to the bare plot. The addition of "fibromat" to the hydroseeding plot resulted in significantly lower soil loss. All hydroseeding plots overlaid with biomats gave better protection, resulting in C factor lower than 0.004. Close turfing produced C factor of 0.004, compared to 0.017 for spot turfing, 0.021 for hydroseeding only, 0.122 for vetiver and 0.213 for legume. From statistical correlation results, soil loss from the bare plot was better correlated with KE>25 than raindepth, EI30 and AIm.